COMPARISON OF CATCH HAND LINE IN THE FISH AGREGATING DEVICE (FAD’s)AND THE OUTSIDE OF FISH AGREGATING DEVICE THE WATERS BENGKALIS PROVINCE RIAU - Rezki, Helmi; Brown, Arthur; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The study was conducted on 07 July - 13 July 2014 in the village of Rhubay District of North Rupat Bengkalis District of Riau Province . The researchmethod is experimentation . This study purpose to determine hand line catches interms of the type and number of catches in fish agregating device(FAD’s) and theoutside of fish agregating device(FAD’s) . The catch in the fish agregating deviceare 19 individuals with an average of 0.71 kg , while the outside of fish agregatingdevice are 23 indivuduals with an average of 0.94 kg . Of the t-test is known thatthe value Thit = 0.76 while Ttab = 2.10092 , this means Thit < Ttab , H0 is accepted .This means that there is no difference catches the fish agregating device andoutside of fish agregating device .Keywords: Hand line, Fish agregating device (FAD’s), Teluk Rhu village,